Exercise-induced cardio-pulmonary remodelling in endurance athletes: Not only the heart adapts. (April 2020) - Domenech-Ximenos, Blanca; Garza, Maria Sanz-de la; Prat-González, Susanna; Sepúlveda-Martínez, Álvaro; Crispi, Fatima; Perea, Rosario J; Garcia-Alvarez, Ana; Sitges, Marta
Background: The cumulative effects of intensive endurance exercise may induce a broad spectrum of right ventricular remodelling. The mechanisms underlying these variable responses have been scarcely explored, but may involve differential pulmonary vasculature adaptation. Our aim was to evaluate right ventricular and pulmonary circulation in highly trained endurance athletes. Methods: Ninety-three highly trained endurance athletes (>12 h training/week at least during the last five years; age: 36 ± 6 years; 52.7% male) and 72 age- and gender-matched controls underwent resting cardiovascular magnetic resonance imaging to assess cardiac dimensions and function, as well as pulmonary artery dimensions and flow. Pulmonary vascular resistance (PVR) was estimated based on left ventricular ejection fraction and pulmonary artery flow mean velocity. Resting and exercise Doppler echocardiography was also performed in athletes to estimate pulmonary artery pressure. Results: Athletes showed larger biventricular and biatrial sizes, slightly reduced systolic biventricular function, increased pulmonary artery dimensions and reduced pulmonary artery flow velocity as compared with controls in both genders ( p  < 0.05), which resulted in significantly higher estimated PVR in athletes as compared with controls (2.4 ± 1.2 vs . 1.7 ± 1.1; p  < 0.05). Substantially high estimated PVR values (>4.2 WU) were found in seven of the 93 (9.3%) athletes: those exhibiting an enlarged pulmonary artery (indexed area cm 2 /m 2 : 4.8 ± 0.6 vs . 3.9 ± 0.6, p  < 0.05), a decreased pulmonary artery distensibility index (%: 43.0 ± 15.2 vs . 62.0 ± 17.4, p  < 0.05) and a reduced right ventricular ejection fraction (%: 49.3 ± 4.5 vs . 53.6 ± 4.6, p  < 0.05). Conclusions: Exercise-induced remodelling involves, besides the cardiac chambers, the pulmonary circulation and is associated with an increased estimated PVR. A small subset of athletes exhibited substantial increase of estimated PVR related to pronounced pulmonary circulation remodelling and reduced right ventricular systolic function.